Estrutura de capital no Brasil: fatores relevantes para cooperativas de crédito - Zancan, Flávia (2021)
The evaluation of the capital structure of credit unions is of fundamental importance to maintain the stability of the financial market. Its relevance comes from the important role of sustaining the capacity of these organizations to absorb losses due to the risks assumed by the business. From this, this study aims to analyze the main determinants of the capital structure of Brazilian credit unions, in the period from 2000 to 2019, in the light of the theories of Trade-Off and Pecking Order. Factors such as size, profitability, growth opportunity, tangibility, deposits, volatility, credit risk, liquidity, gross domestic product, inflation, interbank deposit certificate, and interest rate are evaluated. To assess the capital structure, three dependent variables are considered, total debt, total debt to shareholders' equity and fixed assets. The study population comprises the singular Brazilian credit unions, free to join, totaling 872 organizations evaluated over 20 years (2000 to 2019). To this end, the study is divided into two parts, the first period from 2000 to 2007 and the second from 2008 to 2019, this division is justified by the fact that it is of interest to capture the possible effect of the Subprime Financial Crisis on the capital structure of cooperative financial institutions. For analysis, descriptive statistics, graphic analysis of the capital structure and the estimation model and robustness tests were used, through the method of ordinary least squares with fixed effects. The results show, in general, a tendency for credit unions to maintain leverage levels throughout the twenty years, indicating a certain tendency for profile of total indebtedness and fixed assets in the pre and post period - subprime financial crisis. They were found to be the main determinants of the capital structure of Brazilian credit unions, considering the entire study period, size, profitability, growth opportunity, deposits and inflation. Considering the periods in which the theoretical forecast was confirmed in relation to the total periods analyzed for all variables, it is clear that 59.26% of the assessments with the singular credit unions confirm the theoretical hypotheses of the determinants, with the major part of the variables are in accordance with the assumptions of the Pecking Order Theory.